2008
DOI: 10.1002/mabi.200800122
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Collagen‐Like Sequential Polypeptides Containing O‐Phospho‐L‐Hydroxyproline and Preparation of Electrospun Composite Fibers for Possible Dental Application

Abstract: A synthetic route is described for collagen-like polypeptides constructed from O-phospho-L-hydroxyproline [Hyp(PO(3)H(2))] residues. Using the synthetic polypeptides and a natural protein, gelatin, fine fibers and their network structures (ESNWs) were prepared via electrospinning. The composite ESNWs can induce the mineralization of calcium phosphate. The phosphoryl groups of the Hyp(PO(3)H(2)) residues affect both the crystalline phase and amount of the calcium phosphate, depending on the chemical structure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…We so far employed an excess amount of HBr/AcOH for deprotecion in our previous studies on synthesis of sequential polypeptides, which were often composed of Ser, Tyr, and Lys residues [14][15][16][17]. In the present study, one essential requirement for the deprotection is that the branch-root structure of the conjugate 14, i.e., the ester linkage between the Nˇ-peptydyl-ˇ-Ala (or the NH 2 -free ˇ-Ala) and the parent cellulose must be left unchanged.…”
Section: Removal Of Protecting Groups From Conjugate 14mentioning
confidence: 99%
“…We so far employed an excess amount of HBr/AcOH for deprotecion in our previous studies on synthesis of sequential polypeptides, which were often composed of Ser, Tyr, and Lys residues [14][15][16][17]. In the present study, one essential requirement for the deprotection is that the branch-root structure of the conjugate 14, i.e., the ester linkage between the Nˇ-peptydyl-ˇ-Ala (or the NH 2 -free ˇ-Ala) and the parent cellulose must be left unchanged.…”
Section: Removal Of Protecting Groups From Conjugate 14mentioning
confidence: 99%
“…By means of this approach, the present human hair protein film can be modified as a practical material for implant‐use in hard tissue engineering. The synthetic phosphorylated polypeptides30 are also expected as the candidates for immobilized osteoinductive factors, which can be applied as a composite of the human hair protein film.…”
Section: Resultsmentioning
confidence: 99%
“…As such, electrospun gelatin is often cross-linked or combined with synthetic polymers in order to maintain a fibrous structure. Several studies have demonstrated the use of different cross-linkers to reduce the limitations mentioned above, including 1,6-diisocyanatohexane (HMDI), glutaraldehyde, genipin, and glyceraldehydes [47][48][49][50]. Various studies have also looked at electrospinning gelatin nanofibers from different solutions, including the organic solvents HFP and trifluoroethanol (TFE), as well as formic acid, acetic acid, ethyl acetate and water.…”
Section: Gelatinmentioning
confidence: 99%
“…Electrospun gelatin scaffolds have been used for various applications such as wound healing [59,60], nerve [52,61,62], dental [49], bone [48,50,57,63], dermal tissue engineering applications [64,65] and vascular grafts [66]. Much of the work published on electrospun gelatin scaffolds has been directed towards its use in cardiac tissue engineering applications.…”
Section: Gelatinmentioning
confidence: 99%